Acute cholecystitis presenting with massive intra-abdominal haemorrhage - Aljiffry, Murad M. (Oxford University Press, 2014)
Haemorrhagic cholecystitis is a known rare life-threatening complication of acute cholecystitis. In this case report, we describe clinical presentation and radiological findings of acute cholecystitis presenting with massive intra-abdominal haemorrhage. We present a case of a 57-year-old male presenting to the emergency department with clinical symptoms of acute cholecystitis. Initially, the patient was haemodynamically stable. Gallbladder could not be visualized by ultrasound. Computed tomography with IV contrast showed a large haematoma in the gallbladder fossa, with active extravasation of IV contrast. On angiography the bleeding was localized to a branch of the cystic artery, which was embolized using gelfoam material. The patient was taken to the operating room for an urgent laparotomy and cholecystectomy.